Writing the landscape exposing nature in French women's fiction 1789-1815 - Margrave, Christie (Legenda, an imprint of the Modern Humanities Research Association, 2019)
"Women novelists were among the most popular authors of the First Republic and First Empire, yet they are frequently overlooked in favor of their canonical male counterparts. Their penchant for sentimental novels has led some later critics to take their writing at face value as apolitical and domestic, at odds with France's violent convulsions. Futhermore, their carefully crafted presentation of natural settings has, thus far, been dismissed completely. Yet, as Christie Margrave shows, the natural landscape was far from being a casually chosen backdrop for writers such as Cottin, Genlis, Krüdener, Souza, and Staël. Rather, the 'escape into nature' given to their female protagonists was a means to expose and confront the everyday reality and emotional suffering faced by women in the Revolutionary decade and Napoleonic Empire. By highlighting self-expression, and by celebrating the figure of the melancholic wanderer, the social misfit, or the visionary, in the setting of an often tempestuous Nature, they also exerted substancial influence on the literary Romanticism which was soon to capture the European imagination"--Back cover.